Kepercayaan Sebagai Anteseden Berbagi Pengetahuan - Endyastuti Pravitasari; Sri Raharso (Jurnal Riset Bisnis dan Investasi, 2017)
This study aims to analyze the effect of trust on knowledge sharing among Employees in Telkom Corporate University Center Bandung. A phenomenon employees will be selective for the exchange of knowledge with colleagues. Trust measured by affect based trust and cognition based trust. While, knowledge sharing behavior measured by knowledge donation and collecting. The approach uses the quantitative in total 131 respondents. The results of the analysis highlighted that value of trust in Telkom CorpU Center is in high category with cognitive based trust as the highest dimension of mean. The value of knowledge sharing is in high category with knowledge gathering as the highest dimension of mean. The result also shows significance relationship between trust and knowledge sharing. In order to increase knowledge sharing, trust should improved. Author suggest that leader should telling the truth no matter what, management must build an opportunity to show that teamwork is important as well.